Method for producing sulfide solid electrolytes

JP2026166682APending Publication Date: 2026-10-14IDEMITSU KOSAN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059781
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026166682000002
    Figure 2026166682000002
  • Figure 2026166682000003
    Figure 2026166682000003
  • Figure 2026166682000001
    Figure 2026166682000001
Patent Text Reader

Abstract

The objective is to provide a method for producing a sulfide solid electrolyte that has a good particle size distribution. [Solution] The sulfide solid electrolyte slurry for classification is dried using an air-flow dryer. A method for producing a sulfide solid electrolyte, comprising classifying the sulfide solid electrolyte for classification, which has been dried by the aforementioned drying process, using an air-flow classifier.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a method for producing a sulfide solid electrolyte. [Background technology]

[0002] In recent years, with the rapid proliferation of information-related devices and communication equipment such as personal computers, video cameras, and mobile phones, the development of batteries used as their power sources has become increasingly important. Among batteries, lithium-ion batteries are attracting attention due to their high energy density. Currently available lithium-ion batteries use electrolytes containing flammable organic solvents, necessitating the installation of safety devices to suppress temperature rise during short circuits, as well as improvements in structure and materials to prevent short circuits. In particular, for automotive applications, there is a demand for higher capacity and higher output, making safety considerations for conventional electrolyte-based batteries increasingly important. In contrast, lithium-ion batteries that use a solid electrolyte, making the battery entirely solid, do not use flammable organic solvents within the battery, thus simplifying safety devices and offering advantages in manufacturing cost and productivity.

[0003] Sulfide solid electrolytes are known as solid electrolytes used in lithium-ion batteries. From the standpoint of performance and manufacturing in all-solid-state lithium batteries, sulfide solid electrolytes with small particle sizes are required. In all-solid-state lithium batteries, the positive electrode material, negative electrode material, and electrolyte are all solid, so if the particle size of the sulfide solid electrolyte is small, it is easier to form contact interfaces between sulfide solid electrolytes themselves, and between the active material and the sulfide solid electrolyte, which has the advantage of improving the paths for ion conduction and electron conduction.

[0004] Patent Document 1 describes a method for producing a modified sulfide solid electrolyte powder by using a dry classifier and flowing a powdered sulfide solid electrolyte with a specific airflow. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] International Publication No. 2023 / 276860 brochure [Overview of the project] [Problems that the invention aims to solve]

[0006] This invention has been made in view of the above circumstances, and aims to provide a method for producing a sulfide solid electrolyte that can have a good particle size distribution. [Means for solving the problem]

[0007] The method for producing a sulfide solid electrolyte according to the present invention is: The sulfide solid electrolyte slurry for classification is dried using an air-flow dryer. This is a method for producing a sulfide solid electrolyte, comprising classifying the sulfide solid electrolyte for classification, which has been dried by the aforementioned drying process, using an air-flow classifier. [Effects of the Invention]

[0008] According to the present invention, it is possible to provide a method for producing a sulfide solid electrolyte that has a good particle size distribution. [Brief explanation of the drawing]

[0009] [Figure 1] This is a flowchart illustrating an example of a preferred embodiment of the manufacturing method of this embodiment. [Figure 2] This shows the particle size distribution of the sulfide solid electrolyte obtained in Reference Example 1 and the sulfide solid electrolyte obtained in Example 1. [Modes for carrying out the invention]

[0010] Hereinafter, embodiments of the present invention (hereinafter sometimes referred to as "the present embodiments") will be described. In the present specification, the upper and lower limit values related to numerical ranges of "more than or equal to", "less than or equal to", and "to" are values that can be arbitrarily combined, and the numerical values of the examples can also be used as the upper and lower limit values.

[0011] (Findings obtained by the present inventors to arrive at the present invention) As a result of intensive investigations aimed at solving the above problems, the present inventors have found the following matters and completed the present invention. For sulfide solid electrolytes, it is desired to control the particle size of the sulfide solid electrolyte according to its application. In addition, since both the electrode material and the separator material are applied by converting the sulfide solid electrolyte powder into an ink during the battery manufacturing process, if the sulfide solid electrolyte contains foreign matter such as excessively large particles or coarse metal impurities, uniform application will be hindered. Therefore, the sulfide solid electrolyte is required to be free of foreign matter such as coarse particles and coarse metal impurities.

[0012] In general, classification using a classifier is performed for the purpose of removing foreign matter such as coarse particles and metal impurities from powder, or recovering powder having a desired particle size. The present inventors have found that when classifying a sulfide solid electrolyte, the proportion of foreign matter such as coarse particles and metal impurities contained in the sulfide solid electrolyte may increase, and it may be difficult to recover only the sulfide solid electrolyte having a desired particle size. Furthermore, it has been found that when drying to remove the solvent that may be contained in the sulfide solid electrolyte, the sulfide solid electrolyte tends to aggregate depending on the drying conditions. These phenomena are presumed to be due to the fact that the sulfide solid electrolyte is a highly adherent powder.

[0013] Accordingly, the present inventors have conducted investigations focusing on the cohesive force of sulfide solid electrolytes. In the production method of Patent Document 1, a dry classifier is used to flow powdered sulfide solid electrolyte together with a specific air stream to modify the sulfide solid electrolyte, but there is no description related to flash drying a slurry containing the sulfide solid electrolyte, and the above problem is not addressed.

[0014] Based on the above investigations, the inventors have found that by drying the sulfide solid electrolyte slurry using an air-jet dryer and then classifying it using an air-jet classifier, aggregation of the sulfide solid electrolyte is reduced, and a sulfide solid electrolyte with a good particle size distribution can be obtained.

[0015] (Regarding various forms of this embodiment) The method for producing a sulfide solid electrolyte according to the first embodiment of this present invention is: The sulfide solid electrolyte slurry for classification is dried using an air-flow dryer. This is a method for producing a sulfide solid electrolyte, comprising classifying the sulfide solid electrolyte for classification, which has been dried by the aforementioned drying process, using an air-flow classifier.

[0016] In this specification, "sulfide solid electrolyte" means an electrolyte that contains sulfur atoms and maintains a solid state at 25°C under a nitrogen atmosphere. In this embodiment, the sulfide solid electrolyte is a sulfide solid electrolyte that contains lithium atoms, sulfur atoms, and phosphorus atoms and has ionic conductivity due to the lithium atoms.

[0017] "Sulfide solid electrolytes" include crystalline sulfide solid electrolytes. In this specification, a crystalline sulfide solid electrolyte is a sulfide solid electrolyte in which a peak originating from the solid electrolyte is observed in the X-ray diffraction pattern in X-ray diffraction measurements, regardless of whether or not a peak originating from the raw material of the sulfide solid electrolyte is observed. That is, a crystalline sulfide solid electrolyte includes a crystal structure derived from the solid electrolyte, and may be a part of the crystal structure derived from the solid electrolyte, or may be entirely derived from the solid electrolyte.

[0018] As described above, the method for producing a sulfide solid electrolyte in this embodiment involves drying the sulfide solid electrolyte slurry using an air-jet dryer and then classifying it using an air-jet classifier to obtain a sulfide solid electrolyte having a good particle size distribution.

[0019] The method for producing a sulfide solid electrolyte according to the second embodiment of this embodiment is, in the first embodiment described above, The aforementioned airflow dryer is a spray dryer. That is the case.

[0020] In the method for producing a sulfide solid electrolyte according to this embodiment, if the airflow dryer is a spray dryer, aggregation of the sulfide solid electrolyte is further reduced, and a sulfide solid electrolyte with a better particle size distribution can be obtained.

[0021] A method for producing a sulfide solid electrolyte according to a third embodiment of this embodiment is, in the first or second embodiment described above, Both the airflow dryer and the airflow classifier are equipped with a bag filter. That is the case.

[0022] From the viewpoint of efficiently collecting sulfide solid electrolytes, it is preferable that both the airflow dryer and the airflow classifier be equipped with a bag filter.

[0023] The method for producing a sulfide solid electrolyte according to the fourth embodiment of this embodiment is, in the third embodiment described above, The bag filter provided in the aforementioned airflow classifier is a sintered filter. That is the case.

[0024] If the bag filter in the aforementioned airflow classifier is a sintered filter, it becomes easier to remove foreign matter that may be contained in the sulfide solid electrolyte for classification, and a sulfide solid electrolyte with a better particle size distribution can be obtained.

[0025] The method for producing a sulfide solid electrolyte according to the fifth embodiment of this embodiment is, in the third or fourth embodiment described above, The sulfide solid electrolyte recovered by the bag filter of the aforementioned airflow classifier is used as the electrode. That is the case.

[0026] The method for producing a sulfide solid electrolyte according to this embodiment makes it possible to obtain a sulfide solid electrolyte having a good particle size distribution. This sulfide solid electrolyte does not contain coarse particles or foreign substances such as metal impurities, and can be uniformly applied when in solution or slurry form, making it suitable for use as an electrode.

[0027] The method for producing a sulfide solid electrolyte according to the sixth embodiment of this embodiment is, in any one of the first to fifth embodiments described above, The aforementioned sulfide solid electrolyte slurry for classification is used to pulverize raw material containing lithium atoms, sulfur atoms, and phosphorus atoms. The processed material obtained by the aforementioned grinding is dried. The dried product obtained by the aforementioned drying process is to be calcined, and The calcined product obtained by the aforementioned calcination and the solvent are wet-ground using a pulverizer, thereby obtaining the following: That is the case.

[0028] The method for producing sulfide solid electrolytes according to this embodiment allows for the more efficient production of sulfide solid electrolytes having an argyrodite-type crystal structure. Furthermore, the ionic conductivity of the resulting sulfide solid electrolyte can be further improved.

[0029] The method for producing the sulfide solid electrolyte according to this embodiment will be described in more detail below, following the above-described aspects.

[0030] [Method for producing sulfide solid electrolytes] The method for producing a sulfide solid electrolyte of this embodiment (hereinafter also simply referred to as "the method of production of this embodiment") involves drying the sulfide solid electrolyte slurry for classification using an air-flow dryer, as shown in Figure 1. This is a method for producing a sulfide solid electrolyte, comprising classifying the sulfide solid electrolyte for classification, which has been dried by the aforementioned drying process, using an air-flow classifier.

[0031] (Drying using an air-flow dryer) The manufacturing method of this embodiment includes drying the sulfide solid electrolyte slurry for classification using an air-jet dryer. This reduces aggregation of the sulfide solid electrolyte for classification, and makes it possible to obtain a sulfide solid electrolyte with a good particle size distribution. The sulfide solid electrolyte slurry for classification contains a sulfide solid electrolyte and a solvent. The sulfide solid electrolyte is not particularly limited as long as it contains sulfur atoms and maintains a solid state at 25°C under a nitrogen atmosphere. Commercially available products can be used as is, or they can be manufactured and used. A method for producing a classification sulfide solid electrolyte slurry that can be used in this embodiment will be described later.

[0032] Drying using an airflow dryer can be performed by supplying a sulfide solid electrolyte slurry into an airflow of heated gas. Commercially available airflow dryers such as fluidized bed dryers and spray dryers, which have a mechanism for fluidizing media particles or other media with gas, can be used. As for the above-mentioned airflow dryer, from the viewpoint of further reducing the aggregation of the sulfide solid electrolyte for classification and obtaining a sulfide solid electrolyte with a better particle size distribution, a spray dryer is preferred, and a spray dryer is more preferred, in which a fluid containing the sulfide solid electrolyte slurry for classification is sprayed from a spray nozzle into a drying gas at a predetermined temperature to dry the fluid.

[0033] Examples of spray dryers include those that spray a classification sulfide solid electrolyte slurry from a spray nozzle along with heated gas, and dry it by bringing it into contact with separately heated gas as needed. The above gas is preferably an inert gas. From the viewpoint of availability, nitrogen gas or argon gas is preferred as the inert gas.

[0034] The spray pressure in the spray dryer is preferably 0.01 to 0.8 MPa, more preferably 0.02 to 0.6 MPa, and even more preferably 0.03 to 0.5 MPa. When the spray pressure in the spray dryer is within the above range, the solvent in the sulfide solid electrolyte slurry for classification can be sufficiently removed. Furthermore, aggregation of the sulfide solid electrolyte for classification is further reduced, and a sulfide solid electrolyte with a better particle size distribution can be obtained.

[0035] From the viewpoint of better demonstrating the effects of the present invention, the droplet diameter of the spray liquid in the spray dryer is preferably 50 μm or less, more preferably 45 μm or less, and even more preferably 40 μm or less.

[0036] The operating conditions for the spray dryer can be appropriately determined according to the type of solvent contained in the sulfide solid electrolyte slurry for classification, and since they vary depending on the boiling point of the solvent, etc., they cannot be specified in general terms. However, it is preferable that the temperature of the heated gas that comes into contact with the sulfide solid electrolyte slurry sprayed from the nozzle is 350°C or lower, as this allows the solvent to dry from the sprayed droplets at an appropriate speed and controls the particle size of the sulfide solid electrolyte for classification. It is more preferable that it is 300°C or lower, even more preferable that it is 250°C or lower, and even more preferable that it is 230°C or lower. As a lower limit, from the viewpoint of shortening drying time and improving productivity, it is preferable that the temperature be 80°C or higher, and more preferably 100°C or higher.

[0037] Furthermore, the amount of sulfide solid electrolyte slurry for classification supplied to the nozzle cannot be set uniformly as it may vary depending on the scale of the spray dryer. It should be determined appropriately according to the scale, and is usually around 1 to 60 g / min. From the viewpoint of drying in a shorter time, it is preferably 3 to 50 g / min, more preferably 5 to 40 g / min, and even more preferably 10 to 30 g / min. The operating conditions for the spray dryer can be implemented, for example, by the method described in the examples.

[0038] From the viewpoint of efficiently collecting the dried sulfide solid electrolyte for classification, the airflow dryer is preferably equipped with a bag filter. The fluid containing the gas supplied as a heat transfer medium and the sulfide solid electrolyte for classification that has passed through the airflow dryer can be supplied to the bag filter and recovered.

[0039] The filters used in bag filters are not particularly limited and can be made from materials such as polypropylene, nylon, acrylic, polyester, cotton, wool, heat-resistant nylon, polyamide / polyimide, PPS (polyphenylene sulfide), glass fiber, and PTFE (polytetrafluoroethylene). Functional filters, such as electrostatic filters, can also be used. Among these, filters made from heat-resistant nylon, polyamide / polyimide, PPS (polyphenylene sulfide), glass fiber, and PTFE (polytetrafluoroethylene) are preferred, filters made from heat-resistant nylon, PPS (polyphenylene sulfide), and PTFE (polytetrafluoroethylene) are more preferred, and filters made from PTFE (polytetrafluoroethylene) are particularly preferred.

[0040] The bag filter may have a means for removing debris, for example, a pulsating back pressure method or a pulse jet method is preferred, with the pulse jet method being preferred. Furthermore, an induced draft fan may be installed in the line from the exhaust port of the bag filter to forcibly exhaust the gas being exhausted from the exhaust port.

[0041] (Classification using an airflow classifier) The manufacturing method of this embodiment includes classifying the classification sulfide solid electrolyte, which has been dried by the above-mentioned drying process, using an air-flow classifier. By performing the above classification using an airflow classifier, the sulfide solid electrolyte for classification can be separated into multiple particle groups with different particle sizes, and a sulfide solid electrolyte with a good particle size distribution can be classified.

[0042] Airflow classifiers can be classified into gravity field classifiers, inertial force field classifiers, or centrifugal force field classifiers based on their principles. Any classification method is acceptable, but centrifugal force field classifiers are preferred from the viewpoint of further reducing the aggregation of the sulfide solid electrolyte used for classification. Centrifugal force field classifiers can be further classified into free vortex types such as spiral vortex airflow, vortex airflow (without guide vanes), and vortex airflow (with guide vanes), or forced vortex types such as airflow-type rotating classification chambers and airflow-type rotating vanes. However, from the viewpoint of classification efficiency, classification point adjustment, adhesion inside the machine (improvement of recovery rate), and simplicity of the device, vortex airflow (with guide vanes) classifiers or airflow-type rotating vanes are preferred.

[0043] The above-mentioned airflow classifier is preferably equipped with a bag filter from the viewpoint of efficiently collecting the sulfide solid electrolyte recovered by classification. As the bag filter, the bag filter described as one that can be used in the above-mentioned airflow dryer can be used. Furthermore, the above-mentioned bag filter may be a sintered filter from the viewpoint of easily removing foreign matter that may be contained in the sulfide solid electrolyte for classification and obtaining a sulfide solid electrolyte with a better particle size distribution.

[0044] The sulfide solid electrolyte for classification is supplied into the airflow within the airflow classifier. The sulfide solid electrolyte having the desired particle size distribution, separated by classification, is supplied to the bag filter through piping connected to the bag filter along with the airflow, and is collected (recovered) by the bag filter. The airflow after the recovery of the sulfide solid electrolyte may be returned to the airflow classifier as a circulating airflow.

[0045] From the viewpoint of preventing quality deterioration, the above-mentioned airflow is preferably an inert gas flow. From the viewpoint of availability, nitrogen gas or argon gas is preferred as the inert gas.

[0046] Within the above-mentioned airflow classifier, the pressure can be appropriately selected by the device, and the pressure inside the airflow classifier may be left uncontrolled, or it may be reduced or increased.

[0047] The airflow rate of the above airflow cannot be generalized as it varies depending on the amount of sulfide solid electrolyte supplied to the airflow classifier for classification, but it is usually around 0.8 m 3 More than 0.9 m / min, preferably 0.9 m 3 / min or more, more preferably 1.0m 3 It is more than / min, and the upper limit is usually 1.3m 3 Less than 1.2 m / min, preferably 1.2 m 3 Less than or equal to 1.1 m / min, more preferably 1.1 m 3 It is less than / minute.

[0048] The sulfide solid electrolyte obtained (recovered) by the above classification has an average particle size (D 50 It is preferable that the sulfide solid electrolyte has a particle size of 0.3 μm or more and less than 2.0 μm. In this specification, unless otherwise specified, "average particle size" refers to the particle size (D50, also called median diameter) corresponding to the cumulative frequency of 50% by volume from the smaller particle side in a volume-based particle size distribution based on laser diffraction and light scattering. The above average particle size can be measured specifically by the method described in the examples. Furthermore, it is preferable that the above-mentioned sulfide solid electrolyte exhibits a unimodal particle size distribution based on volume and has a peak in the range of particle size between 0.3 μm and 2.0 μm. The crystal structure of the above sulfide solid electrolyte is the same as that described in the section (Sulfide Solid Electrolytes) below.

[0049] (Application) Since the above-mentioned sulfide solid electrolyte does not contain foreign matter such as coarse particles or metal impurities, it can be uniformly applied when prepared as a solution or slurry, making it suitable for use as an electrode. The above-mentioned sulfide solid electrolyte may be used in the positive electrode layer, the negative electrode layer, or the electrolyte layer. Each layer can be manufactured by known methods. When the above-mentioned sulfide solid electrolyte is used as an electrode mixture, it can be used as an electrode mixture containing the above-mentioned sulfide solid electrolyte and an electrode active material. As electrode active materials, positive electrode active materials and negative electrode active materials are selected depending on whether the electrode composite material is used as the positive electrode or the negative electrode. Conventional materials that have been used as such for the positive and negative electrode active materials can be used. In addition to the sulfide solid electrolyte and electrode active material, the material may also contain other components such as conductive materials and binders.

[0050] When the above-mentioned sulfide solid electrolyte is used as a battery, it can be used as a lithium-ion battery containing at least one of the above-mentioned sulfide solid electrolyte and the above-mentioned electrode composite material. Furthermore, the above-mentioned battery preferably uses a current collector in addition to the positive electrode layer, electrolyte layer, and negative electrode layer, and known current collectors can be used. For example, a layer coated with gold or the like, which reacts with the above-mentioned solid electrolyte, such as Au, Pt, Al, Ti, or Cu, can be used.

[0051] (Method for producing a sulfide solid electrolyte slurry for classification) There are no particular restrictions on the method for producing a sulfide solid electrolyte slurry for classification, but for example, Crushing a raw material containing lithium atoms, sulfur atoms, and phosphorus atoms. The processed material obtained by the aforementioned grinding is dried. The dried product obtained by the aforementioned drying process is to be calcined, and One example of a manufacturing method (hereinafter also referred to as "manufacturing method 1") is one in which the calcined product obtained by the aforementioned calcination and the solvent are wet-ground using a pulverizer. According to the above manufacturing method 1, sulfide solid electrolytes having an argyrodite-type crystal structure can be produced more efficiently.

[0052] [Manufacturing method 1] (To crush) The raw material content should contain solid electrolyte raw materials selected according to the sulfide solid electrolyte to be obtained, and preferably contain lithium atoms, sulfur atoms, and phosphorus atoms. Furthermore, since sulfide solid electrolytes preferably contain halogen atoms from the viewpoint of improving ionic conductivity, it is preferable that the raw material content further contains halogen atoms. More specifically, the raw material content is a content containing substances containing these atoms (hereinafter also referred to as "solid electrolyte raw materials"), and it is preferable that it contains two or more types of solid electrolyte raw materials.

[0053] As solid electrolyte raw materials included in the raw material composition, typically preferred materials include those containing at least two atoms selected from the above atoms, such as lithium sulfide; phosphorus trisulfide (P2S3), phosphorus pentasulfide (P2S5), etc., and those consisting of one atom selected from the above atoms, such as elemental phosphorus or elemental sulfur. Among these, lithium sulfide and phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5) are preferred, and among phosphorus sulfides, phosphorus pentasulfide (P2S5) is preferred.

[0054] The raw material may also contain halogen atoms, and examples of raw materials include substances containing halogen atoms. For example, lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; and elemental halogens such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2) are typically preferred.

[0055] The above-mentioned solid electrolyte raw materials can be used by blending them in a ratio that matches the composition of a sulfide solid electrolyte having a desired crystal structure. Examples of the blending ratio of lithium sulfide contained in the raw material to other solid electrolyte raw materials include those described in International Publication No. 2020 / 105737 (see paragraphs

[0024] to

[0028] ), etc. Furthermore, the solid electrolyte raw materials can also be appropriately selected from the substances exemplified in International Publication No. 2020 / 105737 (see paragraphs

[0020] to

[0022] ), etc.

[0056] For grinding the raw materials, grinders can be used, including container-driven grinders such as ball mills and bead mills, and pin mills are also preferred because they offer short processing times and allow for continuous grinding operations.

[0057] It is preferable to pre-mix the raw materials. There are no particular restrictions on the type of mixer that can be used for pre-mixing, but examples of preferred mixers include mechanical agitators, conical screw type mixers such as Nauta mixers, and high-speed agitators such as FM mixers.

[0058] Furthermore, it is preferable to mix and grind the raw material in a solvent. As the solvent used during mixing and grinding, nonpolar solvents such as hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents, and polar solvents such as solvents containing heteroatoms are preferably used, and it is preferable to use a combination of a nonpolar solvent and a polar solvent. When a combination of a nonpolar solvent and a polar solvent is used, aromatic hydrocarbon solvents, particularly toluene and ethylbenzene, are preferred as the nonpolar solvent, and nitrile solvents that have the property of azeotropic formation with aromatic hydrocarbon solvents such as toluene and are easily removed together with aromatic hydrocarbon solvents such as toluene are preferred as the polar solvent.

[0059] As equipment used for mixing and grinding the raw material components, preferred grinders include the grinders exemplified above as grinders that can be used for grinding the raw materials, planetary ball mills, vibratory mills, rolling mills, bead mills, and the like.

[0060] (To dry) The above manufacturing method 1 includes drying the processed material after grinding. By drying the processed material, a dried product is obtained. The drying process described above is not particularly limited as long as the solvent can be removed from the treated material, but methods using a dryer such as an airflow dryer, spray dryer, or fluidized bed dryer with a medium are preferred. For example, if the drying is performed using an airflow dryer, aggregation of the dried material is further reduced, and a sulfide solid electrolyte with a better particle size distribution is more likely to be obtained.

[0061] (Firing) The above manufacturing method 1 includes calcining the dried product obtained by drying. This makes it possible to produce a sulfide solid electrolyte. The heating temperature during the calcination of the dried material can be appropriately selected according to the composition of the sulfide solid electrolyte to be obtained, for example, preferably 300°C or higher, more preferably over 300°C, even more preferably 320°C or higher, even more preferably 350°C or higher, and particularly preferably 380°C or higher. The upper limit is preferably 470°C or lower, more preferably 460°C or lower, even more preferably 450°C or lower, even more preferably 440°C or lower, and particularly preferably 430°C or lower. The heating time is preferably 1 minute to 6 hours, more preferably 1 minute to 2 hours, and even more preferably 5 minutes to 1 hour.

[0062] The firing process is preferably carried out in an inert gas atmosphere (e.g., a nitrogen atmosphere, an argon atmosphere) or a reduced-pressure atmosphere (especially in a vacuum). Furthermore, firing can be carried out using firing furnaces such as stationary hearth kilns or rotary kilns.

[0063] (Wet grinding) The above manufacturing method 1 includes wet grinding of the calcined product obtained by calcination and the solvent using a pulverizer. A sulfide solid electrolyte slurry for classification is obtained by wet grinding the above-mentioned calcined material and solvent using a pulverizer.

[0064] The above-mentioned pulverizer is, as the name suggests, a device used for pulverization, and while pulverization may also occur simultaneously with stirring and mixing, as shown in Figure 1, the calcined material and solvent may be mixed using a mixer before pulverization. The above-mentioned pulverizer is preferably a wet pulverizer capable of wet pulverization. Typical wet grinders include wet bead mills, wet ball mills, and wet vibratory mills. Wet bead mills, which use beads as the grinding medium, are preferred because they allow for free adjustment of the grinding conditions and are more suitable for materials with smaller particle sizes.

[0065] Furthermore, a flow-type pulverizer can be used that allows for circulating operation to recirculate the slurry to be pulverized as needed. Specifically, this includes a pulverizer that circulates the slurry between a pulverizer (pulverizer / mixer) that pulverizes the slurry and a temperature-maintaining tank (reaction vessel).

[0066] The size of the beads and balls used in the above-mentioned ball mill and bead mill can be appropriately selected according to the desired particle size, processing volume, etc. For example, the diameter of the beads is usually 0.05 mmφ or larger, preferably 0.1 mmφ or larger, more preferably 0.3 mmφ or larger, with an upper limit of usually 5.0 mmφ or smaller, preferably 3.0 mmφ or smaller, and more preferably 2.0 mmφ or smaller. The diameter of the balls is usually 2.0 mmφ or larger, preferably 2.5 mmφ or larger, more preferably 3.0 mmφ or larger, with an upper limit of usually 20.0 mmφ or smaller, preferably 15.0 mmφ or smaller, and more preferably 10.0 mmφ or smaller. Furthermore, the materials used for beads and balls include, for example, metals such as stainless steel, chrome steel, and tungsten carbide; ceramics such as zirconia and silicon nitride; and minerals such as agate.

[0067] When using a ball mill or bead mill, the rotational speed varies depending on the scale of processing and cannot be generalized, but it is usually 10 rpm or more, preferably 20 rpm or more, more preferably 50 rpm or more, and even more preferably 100 rpm or more. The upper limit is usually 2,500 rpm or less, preferably 2,200 rpm or less, more preferably 2,000 rpm or less, and even more preferably 1,800 rpm or less. Furthermore, the grinding time in this case varies depending on the scale of processing and cannot be generalized, but it is usually 0.5 hours or more, preferably 1 hour or more, more preferably 5 hours or more, and even more preferably 10 hours or more. The upper limit is usually 100 hours or less, preferably 72 hours or less, more preferably 48 hours or less, even more preferably 36 hours or less, even more preferably 24 hours or less, and even more preferably 10 hours or less.

[0068] By selecting the size and material of the medium used (beads, balls), as well as the rotor rotation speed and time, mixing, stirring, crushing, or a combination of these processes can be performed, allowing for adjustment of the particle size of the resulting sulfide solid electrolyte.

[0069] (solvent) As the solvent mentioned above, a wide range of solvents that have been conventionally used in the production of solid electrolytes can be adopted, such as hydrocarbon solvents including aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents. In addition to the hydrocarbon solvents mentioned above, other solvents that may be used include those containing atoms other than carbon atoms and hydrogen atoms, such as heteroatoms like nitrogen atoms, oxygen atoms, sulfur atoms, and halogen atoms.

[0070] The amount of solvent used is preferably 100 mL or more, more preferably 200 mL or more, even more preferably 250 mL or more, and even more preferably 300 mL or more per 1 kg of sulfide solid electrolyte, with an upper limit of preferably 3000 mL or less, more preferably 2500 mL or less, even more preferably 2000 mL or less, and even more preferably 1550 mL or less. When the amount of solvent used is within the above range, a sulfide solid electrolyte slurry for classification can be prepared efficiently.

[0071] (Sulfide solid electrolyte) The sulfide solid electrolyte obtained by the above manufacturing method 1 has an argyrodite-type crystal structure. The argyrodite crystal structure is a crystal structure that basically has the structural framework of Li7PS6, with some of the P being replaced by Si. Examples of the composition formula of the argyrodite-type crystal structure include Li 7-x P 1-y Si y S6, Li 7+x P 1-y Si y S6 (x is -0.6 to 0.6, y is 0.1 to 0.6). The argyrodite-type crystal structure represented by these composition formulas is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks that mainly appear at positions of 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°. Note that these peak positions may fluctuate within a range of ±0.5°.

[0072] Examples of the composition formula of the argyrodite-type crystal structure include Li 7-x-2y PS 6-x-y Cl x (0.8≦x≦1.7, 0<y≦-0.25x+0.5). The argyrodite-type crystal structure represented by this composition formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks that mainly appear at positions of 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. Further, examples of the composition formula of the argyrodite-type crystal structure include Li 7-x PS 6-x Ha x (Ha is Cl or Br, x is preferably 0.2 to 1.8). The argyrodite-type crystal structure represented by this composition formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks that mainly appear at positions of 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°.

[0073] Here, since the sulfide solid electrolyte obtained by the above production method 1 preferably contains a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom, the aforementioned "Li 7-x P 1-y Si yS6, Li 7+x P 1-y Si y S6 (x is -0.6 to 0.6, y is 0.1 to 0.6)", when an atom other than a chlorine atom is used as the halogen atom in the composition formula, it may not be represented by the composition formula "Li 7-x-2y PS 6-x-y Cl x (0.8≦x≦1.7, 0<y≦-0.25x+0.5)". However, when the sulfide solid electrolyte obtained by the above production method 1 has the same diffraction peaks as the diffraction peaks described as the diffraction peaks possessed by the aforementioned "argyrodite-type crystal structure", it can be said that the sulfide solid electrolyte preferably has an argyrodite-type crystal structure formed of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms.

[0074] In the sulfide solid electrolyte obtained by the above production method 1, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms is preferably 1.0 to 1.8: 0.1 to 0.8: 1.0 to 2.0: 0.01 to 0.6, more preferably 1.1 to 1.7: 0.2 to 0.6: 1.2 to 1.8: 0.05 to 0.5, still more preferably 1.2 to 1.6: 0.25 to 0.5: 1.3 to 1.7: 0.08 to 0.4.

[0075] When bromine and iodine, or bromine and chlorine are used in combination as halogen atoms, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, bromine, and chlorine (or iodine) is preferably 1.0 to 1.8: 0.1 to 0.8: 1.0 to 2.0: 0.01 to 0.3: 0.01 to 0.3, more preferably 1.1 to 1.7: 0.2 to 0.6: 1.2 to 1.8: 0.02 to 0.25: 0.02 to 0.25, still more preferably 1.2 to 1.6: 0.25 to 0.5: 1.3 to 1.7: 0.03 to 0.2: 0.03 to 0.2, even more preferably 1.35 to 1.45: 0.3 to 0.45: 1.4 to 1.7: 0.04 to 0.18: 0.04 to 0.18. The type of atoms constituting the sulfide solid electrolyte obtained by the above production method 1 and the composition ratio (molar ratio) thereof can be confirmed by, for example, an ICP emission spectrometer.

[0076] There are no particular restrictions on the shape of the sulfide solid electrolyte, but for example, particulate form can be given. The average particle size (D) of the particulate (crystalline) sulfide solid electrolyte. 50 Examples of these ranges include 0.01 μm to 500 μm and 0.1 to 200 μm. [Examples]

[0077] The present invention will now be specifically described with reference to examples, but the present invention is not limited in any way by these examples.

[0078] (Measurement method) (1) Measurement of volume-based particle size distribution and average particle size The average particle size (cumulative frequency 50 vol%; D50), particle size at a cumulative frequency of 10 vol% (D10), and particle size at a cumulative frequency of 90 vol% (D90) of the sulfide solid electrolyte obtained in Reference Example 1 and Example 1 were measured using a laser diffraction scattering particle size distribution analyzer (Horiba, Ltd., LA-950V2 model LA-950S2) as follows, and determined from the resulting particle size distribution integration curve. Dehydrated toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., special grade) was used as the dispersion medium. 50 mL of the dispersion medium was injected into the flow cell of the apparatus and circulated. The sample to be measured was pre-portioned to 20 mg in a screw vial, 1.3 mL of dibutyl ether was added, and the vial was sonicated for 5 minutes in a sealed state. Then, approximately 0.1 mL of the prepared sample was added to the flow cell of the apparatus, and the particle size distribution was measured. Figure 2 shows the particle size distribution of the sulfide solid electrolyte obtained in Reference Example 1 and the sulfide solid electrolyte obtained in Example 1.

[0079] (Example 1: Manufacturing of sulfide solid electrolyte slurry for classification) (Crush) The raw materials used were lithium sulfide (manufactured by Idemitsu Kosan Co., Ltd., 98.5% purity), phosphorus pentasulfide (manufactured by Thermophos, 99.9% purity), lithium chloride (manufactured by Sigma-Aldrich, 99% purity), and lithium bromide (manufactured by Sigma-Aldrich, 99% purity). Lithium sulfide, phosphorus pentasulfide, lithium chloride, and lithium bromide were weighed in a molar ratio of 47.5:12.5:25.0:15.0, totaling 291 g, and placed in a glass container. The container was then roughly mixed by shaking. The roughly mixed raw material was dispersed under a nitrogen atmosphere in a mixed solvent of 3015 mL of dehydrated toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 18.5 mL of dehydrated isobutyronitrile (manufactured by Kishida Chemical Co., Ltd.) to obtain a slurry (containing approximately 10% by mass of the raw material). The slurry was then mixed and ground for 1 hour using a bead mill ("LMZ015 (model number)", manufactured by Ashizawa Finetech Co., Ltd.) to obtain a slurry containing the ground raw material (processed material).

[0080] (Drying, firing) The obtained slurry was transferred to a Schlenk bottle purged with nitrogen, and the solvent was removed by vacuum drying to obtain a dry product. 100g of the above dried material was packed into a Tamman tube (PT2, manufactured by Tokyo Glass Equipment Co., Ltd.) in a glove box under a nitrogen atmosphere. The opening of the Tamman tube was sealed with quartz wool, and the container was further sealed with a stainless steel airtight container to prevent air from entering. The airtight container was then placed in an electric furnace (FUW243PA, manufactured by Advantec Co., Ltd.) and fired. Specifically, the temperature was raised from room temperature to 500°C at a rate of 2.5°C / min (reaching 500°C in 3 hours), and then maintained at 500°C for 10 hours. After that, it was slowly cooled to obtain the fired product.

[0081] (Wet grinding) Next, the obtained calcined product was supplied to a bead mill ("LMZ015 (model number)", manufactured by Ashizawa Finetech Co., Ltd.) into which 9000 mL of dehydrated toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., special grade) had been added. Mixing and grinding was carried out under a nitrogen atmosphere at a rotor speed of 1626 rpm for 0.75 hours to obtain a sulfide solid electrolyte slurry for classification. The average particle size (D) of the sulfide solid electrolyte contained in the obtained slurry was calculated. 50 The diameter was 1.32 μm.

[0082] (Example 1) The sulfide solid electrolyte slurry for classification obtained in Reference Example 1 was dried using a spray dryer ("CNL-3", manufactured by Okawara Chemical Machinery Co., Ltd.) as an airflow dryer, with a drying inlet temperature of 200°C and a spray pressure of 0.3-0.4 MPa to obtain a sulfide solid electrolyte for classification. The obtained sulfide solid electrolyte for classification was fed into a classifier (vortex airflow (with guide vanes), manufactured by Nippon Pneumatic Mfg. Co., Ltd., MP-150), and the nitrogen gas (airflow) introduction pressure was adjusted to 0.6 MPa for classification. The sulfide solid electrolyte having the desired particle size distribution separated by classification was supplied to the bag filter through piping connecting the classifier and the bag filter along with the airflow, and collected by the bag filter. The average particle size (D) of the collected sulfide solid electrolyte was determined. 50 The diameter was 1.17 μm.

[0083] [Table 1]

[0084] The D90 (2.82 μm) of the sulfide solid electrolyte obtained in Example 1 is smaller than that of the sulfide solid electrolyte obtained in Reference Example 1 (4.04 μm), indicating that coarse particles were removed from the sulfide solid electrolyte. Furthermore, as shown in Figure 2, the sulfide solid electrolyte obtained in Example 1 was confirmed to have a good particle size distribution. [Industrial applicability]

[0085] The method for producing a sulfide solid electrolyte according to this embodiment makes it possible to obtain a sulfide solid electrolyte having a good particle size distribution. The obtained sulfide solid electrolyte is suitable for use in lithium-ion batteries, particularly in lithium-ion batteries used in automotive applications, as well as in information-related equipment and communication equipment such as personal computers, video cameras, and mobile phones, and especially in all-solid-state batteries.

Claims

1. The sulfide solid electrolyte slurry for classification is dried using an air-flow dryer. A method for producing a sulfide solid electrolyte, comprising classifying the sulfide solid electrolyte for classification, which has been dried by the aforementioned drying process, using an air-flow classifier.

2. The method for producing a sulfide solid electrolyte according to claim 1, wherein the airflow dryer is a spray dryer.

3. The method for producing a sulfide solid electrolyte according to claim 1 or 2, wherein both the airflow dryer and the airflow classifier are equipped with a bag filter.

4. The method for producing a sulfide solid electrolyte according to claim 3, wherein the bag filter provided in the airflow classifier is a sintered filter.

5. A method for producing a sulfide solid electrolyte according to claim 3 or 4, wherein the sulfide solid electrolyte recovered by the bag filter of the airflow classifier is used as an electrode.

6. The aforementioned sulfide solid electrolyte slurry for classification is used to pulverize raw material containing lithium atoms, sulfur atoms, and phosphorus atoms. The processed material obtained by the aforementioned grinding is dried. The dried product obtained by the aforementioned drying process is to be calcined, and A method for producing a sulfide solid electrolyte according to any one of claims 1 to 5, comprising wet grinding the calcined product obtained by the calcination and the solvent using a pulverizer.

Citation Information

Patent Citations

  • Method for producing reformed sulfide solid electrolyte powder

    WO2023276860A1